Plasminogen activator inhibitor-1 serves an important role in radiation-induced pulmonary fibrosis - Shioya, Sachiko (Exp Ther Med, 2018)
Radiation-induced pulmonary fibrosis is a serious complication. Plasminogen activator inhibitor-1 (PAI-1) has been indicated to be a key factor in the progression of pulmonary fibrosis. In the present study, the effect of PAI-1 deficiency on radiation-induced pulmonary fibrosis was analyzed. Wild-type (WT) and PAI-1-deficient (PAI-1(−/−)) mice were treated with thoracic irradiation of 15 Gy to induce pulmonary fibrosis. Analyses of bronchoalveolar lavage (BAL) fluids were performed 0, 4, 12, 18, and 24 weeks after irradiation. The degree of pulmonary fibrosis was assessed according to the histology of lung tissues and hydroxyproline contents. The results demonstrated that the irradiation of WT mice increased PAI-1 expression in the lungs after 18 weeks and established lung fibrosis at 24 weeks. The number of total cells and transforming growth factor-β levels in BAL fluid were significantly lower at 24 weeks after irradiation in PAI-1(−/−) mice compared with WT mice. Furthermore, histological examination revealed that the extent of pulmonary fibrosis was attenuated in PAI-1(−/−) mice compared with that in WT mice. Hydroxyproline content was also significantly lower in PAI-1(−/−) mice compared with WT mice at 24 weeks after irradiation. In conclusion, PAI-1 serves an important role in the development of radiation-induced pulmonary fibrosis and may represent a novel therapeutic target for pulmonary fibrosis.